2005
DOI: 10.1111/j.1365-2672.2005.02734.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of chromogenic media for the detection of Listeria species in food

Abstract: Aims: The aim of this study was to evaluate the performance of chromogenic agars, Agar Listeria according to Ottaviani and Agosti (ALOA) and Rapid L. mono agar, compared with Oxford agar for the enumeration and detection of Listeria species in food. Methods and Results: A total of 170 food samples were examined using the three plating media. Listeria species were isolated from 63 samples. In contrast to Oxford agar, detection of Listeria colonies on chromogenic media was as good after 24 h of incubation of pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 9 publications
(14 reference statements)
4
19
0
2
Order By: Relevance
“…other than L. monocytogenes and L. ivanovii. Similar results were reported by others (Greenwood et al, 2005;Notermans, Dufrenne, Leimeister-Wachter, et al, 1991).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…other than L. monocytogenes and L. ivanovii. Similar results were reported by others (Greenwood et al, 2005;Notermans, Dufrenne, Leimeister-Wachter, et al, 1991).…”
Section: Discussionsupporting
confidence: 93%
“…Agar Listeria according to Ottaviani and Agosti (ALOA) is based on detecting phosphatidylinositol specific phospholipase C (PI-PLC) activity of L. monocytogenes (Greenwood et al, 2005). Phospholipases of L. monocytogenes are essential determinants of pathogenicity (Marquis, Doshi, & Portnoy, 1995;Smith et al, 1995) and activity of PI-PLC is expressed only by pathogenic L. monocytogenes (Notermans, Dufrenne, Leimeister-Wachter, Domann, &L.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are in accordance with the results reported by other authors (Gouws and Liedemann 2005;Furrer et al 1991) showing a high frequency of Listeria species isolation, mainly L. innocua, from Oxford and PALCAM agar. This has been witnessed in comparative studies using alternative isolation media (Vlaemynck et al 2000;Karpísková et al 2000;Greenwood et al 2005;Pinto et al 2001) and has led to the introduction of improved selective-differential isolation media, such as ALOA (Vlaemynck et al 2000), in updated standard isolation procedures (Anon 2005b), thus enhancing the detection ratio for L. monocytogenes. The isolates under study were recovered between 1999 and 2002, and following the regulations in force at that time, Oxford and PALCAM were used as selective media instead of ALOA, which explains the high recovery of other Listeria spp.…”
Section: Discussionmentioning
confidence: 98%
“…Indeed the commercial regular salt chicken curry meal was the only meal where general growth of psychrotrophs was evident. Although L. grayii is regarded as non-pathogenic it may indicate deterioration in hygiene standards or inadequate process conditions, leading to an increased risk of contamination by other pathogenic Listeria species (Greenwood et al, 2005). Lekroengsin et al (2007) demonstrated that cooking processes, i.e.…”
Section: Discussionmentioning
confidence: 99%